The back door of midnight / : #5 - Chandler, Elizabeth, 1954- (Dark Secrets, 2010)
Anna, away from home and visiting family for the summer, struggles to trust the cute boy next door and deal with the aftermath of her uncle's death, which has caused her aunt's supposed psychic abilities to be exaggerated, and soon realizes if she does not uncover who the murderer is, she might be the next to die.